Perceptions of effort and risk assessment - Vangsness, Lisa Lynn (Kansas State University, 2017)
Although risky decision-making tasks present some a priori risk (i.e., base-rate), decision makers often have an opportunity to modify this level of risk through their behaviors. Broadly speaking, risk can be modified by assigning additional resources to an ongoing task or by engaging in specific risk-mitigation strategies before or after the risky decision is made. The modification of risk requires ongoing awareness of task demands, resource constraints, and risk-mitigation strategies that can be used to adapt behavior over time. This thesis explores risk modification that occurs during difficult tasks. Difficult tasks hold greater risks because they fall at the edge of the decision maker’s abilities and are likely to require a greater number of resources to overcome. As resources are engaged they become unavailable for other tasks or strategies to cope with changing task demands. I studied how individuals monitor risks and develop risk mitigation strategies using a videogame task designed to mirror contingencies that would be encountered in the real world. Results from two experiments that involve this task suggest that decision-makers adequately monitor and develop active strategies for dealing with risks. These strategies change over time and vary as a function of task difficulty and experience.
Keywords: Risk mitigation; Dynamic decision making; Metacognitive judgments; DifficultyRDOs